2009
DOI: 10.1073/pnas.0900971106
|View full text |Cite
|
Sign up to set email alerts
|

5′-triphosphate RNA requires base-paired structures to activate antiviral signaling via RIG-I

Abstract: The ATPase retinoid acid-inducible gene (RIG)-I senses viral RNA in the cytoplasm of infected cells and subsequently activates cellular antiviral defense mechanisms. RIG-I recognizes molecular structures that discriminate viral from host RNA. Here, we show that RIG-I ligands require base-paired structures in conjunction with a free 5-triphosphate to trigger antiviral signaling. Hitherto unavailable chemically synthesized 5-triphosphate RNA ligands do not trigger RIG-I-dependent IFN production in cells, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
343
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(358 citation statements)
references
References 32 publications
12
343
2
1
Order By: Relevance
“…The preference of RIG-I for shorter substrates might explain why influenza virus has been shown to be exclusively recognized by RIG-I unlike most other RNA viruses that normally rely on both RIG-I and MDA5 recognition. All of the molecules we have identified as specifically interacting with RIG-I also contain some dsRNA regions directly adjacent to the triphosphate, supporting conclusions from previous work that this panhandle-type architecture of the RNA molecule may be preferentially recognized by RIG-I (12,13). The identification of the influenza virus NS segment and SeV DI RNA as preferred substrates of RIG-I also agrees with their predicted roles as RIG-I PAMPs on the basis of the U-rich composition of this RNA (22).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The preference of RIG-I for shorter substrates might explain why influenza virus has been shown to be exclusively recognized by RIG-I unlike most other RNA viruses that normally rely on both RIG-I and MDA5 recognition. All of the molecules we have identified as specifically interacting with RIG-I also contain some dsRNA regions directly adjacent to the triphosphate, supporting conclusions from previous work that this panhandle-type architecture of the RNA molecule may be preferentially recognized by RIG-I (12,13). The identification of the influenza virus NS segment and SeV DI RNA as preferred substrates of RIG-I also agrees with their predicted roles as RIG-I PAMPs on the basis of the U-rich composition of this RNA (22).…”
Section: Discussionsupporting
confidence: 88%
“…Some viruses, such as picornaviruses and influenza virus, appear to be recognized by only one of the sensors, with picornaviruses being sensed by MDA5 and influenza viruses by RIG-I (1,8,9). The substrate specificities of RIG-I and MDA5 have not been clearly established, although from RNA transfection experiments in knockout cells it appears that RIG-I recognizes RNA of various lengths with 5′-triphosphates and some partial double-stranded characteristics, whereas MDA5 senses only very long dsRNA molecules (>2,000 nt) in a phosphate-independent manner (10)(11)(12)(13)(14). All RLRs are members of the DExD/H family of RNA helicases and contain an ATP-dependent helicase domain and a C-terminal regulatory domain (RD).…”
Section: T He Retinoic Acid Inducible Gene I (Rig-i)-like Receptor (Rlr)mentioning
confidence: 99%
See 1 more Smart Citation
“…S3B) (40). These results are consistent with the model that cellular antiviral helicases require an exposed 5′ triphosphate, with additional secondary structure and length requirements (41)(42)(43).…”
Section: Resultssupporting
confidence: 90%
“…Recent studies however, challenged this hypothesis and demonstrated that activation of RIG-I requires base pairing of the nucleoside carrying the 5'ppp. Evidence was provided that RIG-I is triggered by double-stranded, but not single-stranded, RNA containing 5'ppp [35,36]. In addition, Goubau et al showed that also 5'-diphosphate (5'pp) dsRNA serves as an RIG-I ligand, thereby concluding that a minimal feature for RIG-I activation is a base-paired RNA with a free 5'pp [37].…”
Section: In Vitro Transcribed (Ivt) Mrnamentioning
confidence: 99%